Flexibility in Europe's power sector - an additional requirement or an automatic complement? - Joachim Bertsch; Christian Growitsch; Stefan Lorenczik; Stephan Nagl (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The EU member states have declared to strongly increase the share of Renewable Energy Sources in the next decades. Given a large deployment of wind and solar capacities as well as limited cost-efficient storage technologies, this has two major impacts on electricity systems. First, the electricity system has to be flexible enough to cope with the volatile RES-E generation i.e. ramp up supply or ramp down demand on short notice. Second, sufficient back-up capacities are needed for times with low feed-in from wind and solar capacities. The provision of both back-up capacity has been intensively discussed in the previous literature of recent years (for instance Cramton and Stoft, 2008 and Joskow, 2008). In addition, Lamadrid et al (2011) argue that with increasing volatility, incentives to invest in flexible resources should be implemented in market design. However, they did not have a look at the dynamic view in an integrated analysis necessary to to answer the questions of how an electricity system can adapt to an increasing share of renewables. This paper therefore analyses the flexibility requirements of the future European electricity system and the policy implications for market design with a system-economic dynamic approach. For this purpose, we simulate the development of the European electricity markets up to 2050 by using a linear investment and dispatch optimization model. Flexibility requirements are implemented in the model via constraints for ramping and provision of balancing power. We find that although an increase of fluctuating renewables has a tremendous impact on volatility and therefore flexibility requirements, the main trigger for investments into flexible conventional capacity are the achievable full load hours rather than ramping capabilities. Therefore any market design with investment incentives of achievable full load hours does not need additional incentives for flexibility.
Keywords: D02; C63; Q40; 330